Towards the integration of IT/OT technologies in Electricity Based Digitalized Energy Systems - Negi, Mansi (My University, 2024)
This integration of information technology (IT) and operational technology (OT) in electricity based digitalized energy systems (EBDES) holds significant influence in data driven deci-sion making, improved real time monitoring, and increased operational efficiency. How-ever, this integration also introduces numerous complicated challenges notably with regards to interoperability, cybersecurity issues, and effective deployment of advanced technologies like machine learning (ML) and artificial intelligence (AI). Additionally, the study emphasises on the increasing cybersecurity threats to the energy systems due to the digitalization. It further explores the role of energy components in energy systems and challenges associated with it, highlights the critical role of energy components in the integration of IT and OT and cybersecurity challenges associated with it- variable frequency drive (VFD). The study also investigates the role of programmable logic controllers (PLC) and supervisory control and data acquisition (SCADA) systems with the integration of IT and OT. PLC and SCADA are critical parts of industrial control systems and are crucial for enabling automation, real time monitoring and control of infrastructures. The research underscores the importance of implementing the best cyber security practices to enable this industrial automation that facilitates secure digitalized monitoring and control of operation technology. Further, the study emphasizes the necessity of an integrated strategy that incorporates investments in the adoption of technologies that enable modernization of current energy systems. The findings of this thesis call for the adoption of advanced technologies such as AI and machine learning, IoT devices and blockchain technology to add security features towards system resilient against cyber-attacks. This thesis examines these reported issues by using a mixed method approach, that utilizes triangulation analysis method for the study and integrates quantitative data from surveys of energy professionals with qualitative data from workshops and interviews. The results reflect that integration enables predictive maintenance and allows flexible responses to operational changes, but interoperability is still a significant challenge be-tween IT and OT integration in digitalized energy systems specifically dependent on OT role in these critical infrastructures, with emphasizing the criticality of cybersecurity in vulnerable energy systems.
Keywords: technology; renewable energy sources; information technology; energy systems; energy; intelligent systems; data security; energy technology; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master´s Programme in Smart Energy